Short and long term outcomes of cardiac amyloidosis patients listed for heart transplantation in the united states: a propensity-matched analysis. (14th October 2021) - Akintoye, E; Alvarez, P; Briasoulis, A
Abstract: Background: Heart transplantation (HT) in cardiac amyloidosis (CA) patients has been historically controversial due to the risk of amyloid recurrence. However, recent single-center experiences suggest good outcomes in carefully selected patients. We sought to evaluate contemporary outcomes of CA patients listed for HT in the U.S. and evaluate predictors of survival Methods: Using data from the United Network for Organ Sharing database on adult patients listed for a donor heart in the U.S. between 2010 and 2019, we identified 3 cohorts of patients, namely CA, dilated cardiomyopathy (DCM), and non-CA restrictive cardiomyopathy (RCM). Propensity-match analysis was used to compare primary outcomes of waitlist mortality and post-transplant graft survival between CA and DCM. Results: Over the study period, 411 CA patients (mean age 62.7 years, 16.1% female) were added to the waitlist. In the propensity-matched cohorts, the rates of waitlist mortality were 33.7, 15.8, and 15.6 per 100 person-years for CA, DCM, and non-CA RCM, respectively. Compared to DCM, there was significantly higher waitlist mortality for CA (HR=1.75, 95% CI=1.16–2.65). Over the study period, 330 CA patients were transplanted with donor hearts. The 1-year graft survival rates for CA, DCM, and non-CA RCM were 89%, 92%, and 86%, respectively; and 5-year graft survival rates were 78%, 82%, and 76%, respectively. Graft survival for CA was significantly worse than DCM (HR=1.46, 1.03–2.08), and the two most significant risk factors for poor graft survival among CA patients were renal failure requiring dialysis while on the waitlist (HR=5.4, 1.6–17) and prior history of malignancy (HR=1.7, 1.0–29). CA patients with neither of the risk factor had 1- and 5-year graft survival that is comparable to those of DCM (HR=1.18, 0.81–1.74). On the other hand, CA patients with either of the risk factor had 1- and 5-year graft survival of 81% and 65%, respectively, (HR=2.33, 1.40–3.87, compared to DCM). Conclusion: CA patients experience higher waitlist mortality and worse post-transplant graft survival compared to DCM. However, we identified two risk factors that can be used for further risk-stratification in these patients to achieve comparable graft survival as DCM. Funding Acknowledgement: Type of funding sources: None.